Traumatic right diaphragmatic hernia in children: Diagnostic difficulties - O Ndour; H Mustapha; N A Ndoye; A L Faye Fall; G Ngom; M Ndoye (Wolters Kluwer Medknow Publications, 2015)
Traumatic right diaphragmatic hernia is rare in children. Its diagnosis can be difficult in the acute phase of trauma because its signs are not specific, especially in a poly trauma context. We report two cases of traumatic right diaphragmatic hernia following a blunt thoraco-abdominal trauma, highlighting some difficulties in establishing an early diagnosis and the need for a high index of suspicion.